Effects of High-Fat Diet During Childhood on Precocious Puberty and Gut Microbiota in Mice - Bo, Tingbei; Liu, Min; Tang, Liqiu; Lv, Jinzhen; Wen, Jing; Wang, Dehua (Frontiers in Microbiology, 2022)
Precocious puberty mostly stems from endocrine disorders. However, more and more studies show that a high-fat diet (HFD) is closely related to precocious puberty, but its mechanism is unknown. Since gut microbiota is associated with hormone secretion and obesity, it inspires us to detect the mechanism of gut microbiota in triggering precocious puberty. The model of precocious puberty was established by feeding female mice with an HFD from 21 days old. After puberty, the serum hormone levels, gut microbiome sequencing, and metabolomics were collected. DNA was extracted from feces, and the V3–V4 region of the bacterial 16S rRNA gene was amplified, followed by microbial composition analysis. Subsequently, associations between precocious puberty and the microbiota were determined. We found that (1) HFD after weaning caused precocious puberty, increased serum estradiol, leptin, deoxycholic acid (DCA), and gonadotropin-releasing hormone (GnRH) in the hypothalamus; (2) Through correlation analysis, we found that GnRH was positively correlated with Desulfovibrio, Lachnoclostridium, GCA-900066575, Streptococcus, Anaerotruncus, and Bifidobacterium, suggesting that these bacteria may have a role in promoting sexual development. (3) “HFD-microbiota” transplantation promoted the precocious puberty of mice. (4) Estrogen changes the composition and proportion of gut microbiota and promotes precocious puberty. Therefore, the effect of HFD on precocious puberty is regulated by the interaction of gut microbiota and hormones.